Aplikasi Etika Bisnis dalam Kegiatan UMKM Berdasarkan Perspektif Ekonomi Islam: Application of Business Ethics in MSME Activities Based on an Islamic Economic Perspective - Anugrah Vitra Fadian Afandi; Dafa Aditya Husodo; Farras Rafi Niswara; Adnan Faisal Syaifudin; Lafith Baror Isthibar; Muhammad Abbdee Negara; Ahmad Nurrohim (Litera Academica Publishing, 2024)
This study aims to analyse the Application of Business Ethics in MSME Activities Based on Islamic Economic Perspectives. The business world functions as a social activity that must apply the ethics that apply in society. Where business actors need to strive to keep away from abuse only for personal gain without caring about others, even harming the nation. The application of Islamic business ethics must also be implemented in every aspect of the economy including in the implementation of production, consumption and distribution. The method used in the research is literature study by analysing several journal sources relevant to the research topic. The results show that the implementation of Islamic business ethics in micro, small and medium enterprises (MSMEs) is an important aspect that not only affects the sustainability of the business, but also the character building and integrity of business actors. Aspects of Islamic business ethics relevant to MSMEs are honesty, social responsibility, transparency. The influence of Islamic business ethics on micro, small, and medium enterprises (MSMEs) is very significant, especially in building reputation, customer trust, and business sustainability. One of the main effects of Islamic business ethics is the increase of trust from customers.